Improving English Speaking Skills of Fourth Grade Elementary School Students Through Contextual Problem-Based Mobile-Assisted Language Learning Media - Yutami, Ni Wayan Nindya; Widiana, I Wayan (Mimbar Ilmu, 2024)
This study was motivated by the low English speaking skills of students and the less than optimal use of learning media in learning activities. The purpose of this study was to create learning media that can improve the speaking skills of fourth grade elementary school students in English. This study used the ADDIE model. The subjects were material experts, learning media experts, practitioners, and students in fourth grade of elementary school. The purpose was to measure their level of English speaking skills. Data were collected through observation, interviews, and questionnaires. Observation guidelines, interview guidelines, assessment scale sheets, and questionnaire sheets were the tools used to collect data. A total of 34 students from fourth grade of elementary school were involved in the product trial. To determine the effectiveness of the product, a t-test with correlated samples was used to analyze data from the pre- and post-test results. The results showed that the mobile-assisted language teaching tool (MALL) based on contextual problems was valid. Thus, the results of expert and practitioner evaluations determine the validity and effectiveness of the developed contextual problems.